Flash chronopotentiometric sensing of the polyions protamine and heparin at ion-selective membranes - Gemene, K.; Bakker, Eric (Elsevier, 2009)
We report here on a highly sensitive and rapid detection technique, multipulse flash chronopotentiometry, for the anticoagulant polyion heparin and its antidote protamine. The technique is based on a localized titration of the polyions at the surface of an appropriately formulated polymeric ion-selective membrane devoid of ion exchange properties to prohibit spontaneous extraction processes. A defined ion flux from the sample side to the membrane is induced electrochemically by applying a current pulse of appropriate amplitude and sign. The resulting depletion of the measured ions at the membrane surface gives rise to a characteristic limiting current or transition time and is observed as an inflection point in the resulting chronopotentiogram. The limiting current and the square root of the transition time are linear functions of the concentration of the polyion and yield sensitive and rapid analytical information attractive for clinical diagnostics applications. The polyion protamine is detected in 10-fold diluted blood samples in a matter of seconds via a cathodic current pulse. The utility of the technique for monitoring heparin/protamine titrations in physiological saline solutions is demonstrated.